A multifrequency study of the active star-forming complex NGC6357 - I. Interstellar structures linked to the open cluster Pis24 - Cappa, Cristina Elisabet (2011)
We investigate the distribution of gas (ionized, neutral atomic and molecular) and interstellar dust in the complex star-forming region NGC6357 with the goal of studying the interplay between the massive stars in the open cluster Pis24 and the surrounding interstellar matter. Our study of the distribution of the ionized gas is based on narrow-band Hα, [S II]and [O III] images obtained with the Curtis-Schmidt Camera at CTIO, Chile, and on radio continuum observations at 1465 MHz taken with the VLA with a synthesized beam of 40arcsec. The distribution of the molecular gas is analysed using 12CO(1-0) data obtained with the NANTEN radiotelescope, Chile (angular resolution = 2.7arcmin). The interstellar dust distribution was studied using mid-infrared data from the GLIMPSE survey and far-infrared observations from IRAS. NGC6357 consists of a large ionized shell and a number of smaller optical nebulosities. The optical, radio continuum, and near- and mid-IR images delineate the distributions of the ionized gas and interstellar dust in the H II regions and in previously unknown wind-blown bubbles linked to the massive stars in Pis24 revealing surrounding photodissociation regions. The CO line observations allowed us to identify the molecular counterparts of the ionized structures in the complex and to confirm the presence of photodissociation regions. The action of the WR star HD157504 on the surrounding gas was also investigated. The molecular mass in the complex is estimated to be (4 ± 2) × 105 M⊙. The mean electron densities derived from the radio data suggest electron densities >200 cm-3, indicating that NGC6357 is a complex formed in a region of high ambient density. The known massive stars in Pis24 and a number of newly inferred massive stars are mainly responsible for the excitation and photodissociation of the parental molecular cloud.